A comparison of the cranial nerves and bloodvessels of Dermophis mexicanus and Dermophis gregorii - De Jager, E. F. J.(Emerentia Frederika Jakoba) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1937.